The Influence of Heritage Image, Destination Image, and Experiential Quality on Behavioural Intentions of Foreign Tourists - Junarta, Harbyanto; Nuryakin, Nuryakin; Fatmawati, Indah (JDM (Jurnal Dinamika Manajemen), 2021)
The research was conducted to examine heritage image models, destination images, and experiential quality in influencing touristsÃ¢â‚¬â„¢ behavioral intentions in Kuta Mandalika beach, Lombok. Kuta Mandalika Lombok beach was the object of this research, while this study subjects were foreign tourists. The sampling was carried out by a purposive sampling technique. The number of samples in this study was 133 respondents. The data analysis used Structural Equation Modeling with AMOS as an analysis tool. The research results indicated a positive effect of heritage image toward the experiential quality, positive effect of destination image toward the experiential quality, and positive effect of experiential quality on revisit intentions.Ã‚Â